Pelatihan Deteksi Boraks dan Formalin Menggunakan Indikator Alami di SMA Islam Plus Musthofa Kamal Lombok Timur - Affan Gaffar; Ziana Warsani; Lalu Amrullah; Soufa Malita; Rahayu Safitri Rahman (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2023)
Food safety is often associated with health, especially about food poisoning. Cases of food poisoning often occur in Indonesia with a high incidence rate. One of the causes of food poisoning is the presence of food additives such as formaldehyde, borax, and textile dyes in food. To find out whether or not there is borax and formalin in food, a laboratory test must be carried out. However, laboratory tests require quite a lot of money. Therefore the purpose of this community service is to educate the public about hazardous chemicals used for food preservatives and provide training to detect borax and formalin using natural ingredients from plants with fairly accurate results qualitatively. The method used is an experimental method with a laboratory approach which will be carried out with a series of experiments. The ingredients used include turmeric and dragon fruit skin. The food samples analyzed in this activity were crackers, tofu and meatballs which were taken randomly from traders in the montong betok market, East Lombok. The result of this service is that people are educated about hazardous chemicals that are still used by people as preservatives and people are able to detect borax and formaldehyde in food using natural indicators.